MENINGKATKAN HASIL BELAJAR PKN TENTANG SIMBOL PANCASILA MENGGUNAKAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) DI KELAS II SDN 8 KABILA KABUPATEN BONE BOLANGO - Saripi, Wanda; Pomalingo, Samsi; Ismail, Reska Putri (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to improve the learning outcomes of Citizenship Education (PKn) regarding the symbols of Pancasila in the second grade of SDN 8 Kabila, Bone Bolango District, through the implementation of the Project Based Learning (PjBL) model. The research method used is Classroom Action Research (CAR), conducted in two cycles. In the first cycle, the student mastery rate only reached 37.5%, with 68.75% of students not achieving the minimum competency criteria. This condition indicates a lack of student engagement in the learning process. Therefore, in the second cycle, the PjBL model was applied to enhance active student participation. Evaluation results showed a significant improvement, with student mastery increasing to 81.25% in the second cycle. Additionally, the use of Digital Flipbook media as a learning aid also had a positive impact on students' interest and understanding. This research concludes that the implementation of the PjBL model and interactive media can enhance students' learning outcomes, encouraging them to be more active and creative in understanding Pancasila material. These results indicate that innovative and enjoyable learning strategies are crucial in citizenship education.